2018
DOI: 10.1002/jat.3663
|View full text |Cite
|
Sign up to set email alerts
|

Altered thyroid hormone levels affect body condition at metamorphosis in larvae of Xenopus laevis

Abstract: Chemical, physical and biological environmental stressors may affect the endocrine system, such as the thyroid hormone (TH) axis in larval amphibians with consequences for energy partitioning among development, growth and metabolism. We studied the effects of two TH level affecting compounds, exogenous l-thyroxine (T ) and sodium perchlorate (SP), on various measures of development and body condition in larvae of the African clawed frog (Xenopus laevis). We calculated the scaled mass index, hepatosomatic index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 87 publications
(151 reference statements)
1
15
0
Order By: Relevance
“…As the substance concentrations tend to decrease over time, we provided static‐renewal conditions analysis every 48 hr. Other studies found methimazole and T4 were found stable during the exposure period (Degizt et al, ; Ruthsatz et al, ). However, the chemical stability of the test substances from this study needs to be confirmed from known stability data (Degizt et al, ).…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…As the substance concentrations tend to decrease over time, we provided static‐renewal conditions analysis every 48 hr. Other studies found methimazole and T4 were found stable during the exposure period (Degizt et al, ; Ruthsatz et al, ). However, the chemical stability of the test substances from this study needs to be confirmed from known stability data (Degizt et al, ).…”
Section: Methodsmentioning
confidence: 80%
“…Other studies found methimazole and T4 were found stable during the exposure period (Degizt et al, 2005;Ruthsatz et al, 2018).…”
Section: The Two Leptodactylid Species Have Typical Pond Larvae Of Ortonmentioning
confidence: 85%
“…The SMI accounts for the allometric relationship between mass and a body structure, and is a standardized measure of the body condition that can be directly compared among individuals (Peig and Green 2009, 2010; MacCracken and Stebbings 2012). The SMI has been previously employed as a condition index in anuran larvae (Mac-Cracken and Stebbings 2012;Dittrich et al 2016;Ruthsatz et al 2018b;Ruthsatz et al 2019). A high SMI suggests larger energy storages and, thus, a good body condition.…”
Section: Body Conditionmentioning
confidence: 99%
“…Any increase in temperatures above this optimum increases SMR and may lead to a small but constant increase in energetic demands. Potential consequences of increased metabolic expenditures in a resource-limited, high density system are reduced growth, developmental rates, or larval survival, which could ultimately affect recruitment to the terrestrial habitat (Rowe and Crandall 2018;Ruthsatz et al 2018b). In contrast to TH level and temperature effects on SMR, effects on body condition were distinct.…”
Section: Altered Th Levels and Higher Temperatures Affect Smr And Bodmentioning
confidence: 99%
See 1 more Smart Citation